1993
DOI: 10.1109/76.257216
|View full text |Cite
|
Sign up to set email alerts
|

Transform coding of monochrome and color images using trellis coded quantization

Abstract: The application of transform coding using trellis coded quantization (TCQ) to encode monochrome and color images is investigated. Specifically, TCQ is used to encode transform coefficients resulting from applying a 16 X 16 discrete cosine transform (DCT) to 8-b gray level and 24-b color images. For the color images, the red, green, and blue (RGB) planes are transformed into the NTSC transmission primaries (Y, I, and Q) before the DCT is applied. Rate allocation schemes for encoding the transform coefficients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Due to its excellent MSE performance and moderate complexity, TCQ-based schemes have been widely applied to image compression [2]- [5]. Among these, Marcellin et al combined the DCT with fixed-rate TCQ and entropy-constrained TCQ (ECTCQ) in [2]. They also combined the wavelet transform with ECTCQ in [3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent MSE performance and moderate complexity, TCQ-based schemes have been widely applied to image compression [2]- [5]. Among these, Marcellin et al combined the DCT with fixed-rate TCQ and entropy-constrained TCQ (ECTCQ) in [2]. They also combined the wavelet transform with ECTCQ in [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, [29] designed an image coder which uses TCQ to encode the coefficients resulting from the application of the 2-D DCT. For encoding the "Lenna" image, it is shown that peak signal-to-noise ratios (PSNR) of 39.33, 35.97, and 32.49 dB are obtained at encoding rates of 1.0, 0.5, and 0.25 bits/pixel, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Varying levels of compression can be achieved by using variable quantization of these coefficients. Other compression algorithms, such as improved quantization of the DCT [2] and wavelet transform compression [3], are much superior both visually and in terms of mean square error, but are not yet image processing standards like JPEG.…”
Section: Jpeg Image Compressionmentioning
confidence: 99%